No association between the COMT Val158Met polymorphism and the long‐term clinical response in obsessive–compulsive disorder in the Japanese population. (26th May 2015) - Umehara, Hidehiro; Numata, Shusuke; Tajima, Atsushi; Kinoshita, Makoto; Nakaaki, Shutaro; Imoto, Issei; Sumitani, Satsuki; Ohmori, Tetsuro
<x xml:space="preserve">Abstract</x> Objective Catechol‐O‐methyltransferase (COMT) is an enzyme that participates in the metabolic inactivation of dopamine and norepinephrine, and the Met allele of the COMT Val158Met polymorphism is associated with lower enzymatic activity. The purpose of the present study was to investigate whether this functional variant is associated with obsessive–compulsive disorder (OCD) and the clinical responses in OCD. Methods We first performed a case‐control association study between the COMT Val158Met polymorphism and OCD (171 cases and 944 controls). Then, we examined the association between this polymorphism and the clinical responses in 91 of the OCD patients. Results Our study did not find a significant association between the Met allele and OCD risk or between the Met allele and clinical responses (p > 0.05). Conclusion The present case‐control/pharmacogenetic study did not provide clear evidence that the COMT Val158Met polymorphism is a predictor of OCD or of OCD patients' clinical responses. Copyright © 2015 John Wiley & Sons, Ltd.